Aircraft design projects : for engineering students - Jenkinson, Lloyd R. (Butterworth-Heinemann, 2003)
Written with students of aerospace or aeronautical engineering firmly in mind, this is a practical and wide-ranging book that draws together the various theoretical elements of aircraft design - structures, aerodynamics, propulsion, control and others - and guides the reader in applying them in practice. Based on a range of detailed real-life aircraft design projects, including military training, commercial and concept aircraft, the experienced UK and US based authors present engineering students with an essential toolkit and reference to support their own project work. All aircraft projects are unique and it is impossible to provide a template for the work involved in the design process. However, with the knowledge of the steps in the initial design process and of previous experience from similar projects, students will be freer to concentrate on the innovative and analytical aspects of their course project. The authors bring a unique combination of perspectives and experience to this text. It reflects both British and American academic practices in teaching aircraft design. Lloyd Jenkinson has taught aircraft design at both Loughborough and Southampton universities in the UK and Jim Marchman has taught both aircraft and spacecraft design at Virginia Tech in the US. * Demonstrates how basic aircraft design processes can be successfully applied in reality * Case studies allow both student and instructor to examine particular design challenges * Covers commercial and successful student design projects, and includes over 200 high quality illustrations.